x-1=2x-17/7

Simple and best practice solution for x-1=2x-17/7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-1=2x-17/7 equation:


x in (-oo:+oo)

x-1 = 2*x-(17/7) // - 2*x-(17/7)

x-(2*x)+17/7-1 = 0

x-2*x+17/7-1 = 0

10/7-x = 0 // - 10/7

-x = -10/7 // * -1

x = 10/7

x = 10/7

See similar equations:

| Y=x^2+kx-k | | 4y=-12x+20 | | 3+29n= | | 4-a+5a=4-7a | | 0=2x-7/87 | | 23.1+-9.81= | | -2p^2+11p-9=0 | | -3G-9=-24 | | 8x+9y=150 | | 6-12n=2 | | [4x+6]+[7x+15]=120 | | 3v=64-5v | | 2.3+5x=3x-5.7 | | 7(x-2)=3+3x | | 19=x-7 | | 14=3/2x-7 | | x/456=4 | | x/4456=4 | | 2x-14=2(2x+3) | | 9x-7=23x-14 | | x-2.6=7.3 | | 27=46+2x-1x | | 1.5m=0.5 | | -6x-21+9x=42 | | 2x+6=-7x-9 | | 27-(x+9)=4x-2 | | 6x-(2x+4)-(x+3)= | | 7(2y+1)=2(y-13) | | 0.4=0.75+y | | -6b+5(1-b)=-8b+26 | | (2x-1)(x^2-3x+5)=0 | | 3(2x+1)+1+2x=3(2x+2)+x |

Equations solver categories